Overweight is a predictor of long-term survival in hospitalised patients with exacerbations of COPD. (July 2016) - Stoll, Paul; Foerster, Saskia; Virchow, J. Christian; Lommatzsch, Marek
Abstract: Background: Although hospitalisations due to an exacerbation of chronic obstructive pulmonary disease (COPD) are associated with increased risk of mortality, there is little information on long-term survival after severe COPD exacerbations. Methods: The 5-year and 8-year overall survival after hospitalisation due to a COPD exacerbation was explored. In addition, potential predictors of survival were analysed. Results: The 57 patients with COPD included in this analysis had a median age of 70 years, a median smoking history of 30 pack years and a median forced expiratory volume in the first second (FEV1 ) of 41.6% predicted at the time of COPD exacerbation. The majority of the patients had either normal weight (body mass index, BMI 18.5–24.99 kg/m 2 : 42%) or overweight (BMI ≥ 25 kg/m 2 : 54%). The 5-year overall survival after exacerbation was 54%, the 8-year overall survival 42%. The presence of cardiac comorbidities, a FEV1 <50% predicted, an age >70 years and a BMI <25 kg/m 2, but not smoking history or current smoking, were associated with decreased overall survival. Multivariate regression analysis revealed that only BMI, age and FEV1 were independent predictors of long-term survival. Overweight patients (BMI ≥ 25 kg/m 2 ) had a substantially higher 5-year overall survival (74%) than patients with a BMI < 25 kg/m 2 (31%). Conclusion: Nearly half of the patients hospitalised due to an exacerbation of COPD die within 5 years after the event. Overweight is a positive predictor of long-term survival in these patients. Highlights: The 5-year overall survival after a severe exacerbation of COPD was 54%. The BMI, age and FEV1 are independent predictors of long-term survival. Overweight is a positive survival predictor in patients with COPD exacerbations.